2016
DOI: 10.1097/nnr.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance, Daytime Symptoms, and Functional Performance in Patients With Stable Heart Failure

Abstract: Background Sleep disturbance is common among patients with heart failure (HF) who also experience symptom burden and poor functional performance. Objective We evaluated the extent to which sleep-related, daytime symptoms (fatigue, excessive daytime sleepiness, and depressive symptoms) mediate the relationship between sleep disturbance and functional performance among patients with stable HF. Methods We recruited patients with stable HF for this secondary analysis of data from a cross-sectional, observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 42 publications
(69 reference statements)
2
50
2
Order By: Relevance
“…Some studies showed that fatigue was prevalent among patients with HF, ranging from 45.8 to 100% (Austin et al, 2011, Perez-Moreno et al, 2014, Nasiri et al, 2016, Tang et al, 2010. The participants in this study seemed to have a lower mean global fatigue index/GFI (22.99), ranging from 10 -44 on the MAF than several studies in USA (29.8 to 35.08) (Jeon and Redeker, 2016, Redeker et al, 2010b, Redeker et al, 2012, Fritschi and Redeker, 2015. Findings from another study by Nasiri et al (2016) revealed a lower score of GFI among patients with HF in Iran (5.92).…”
Section: Discussioncontrasting
confidence: 44%
“…Some studies showed that fatigue was prevalent among patients with HF, ranging from 45.8 to 100% (Austin et al, 2011, Perez-Moreno et al, 2014, Nasiri et al, 2016, Tang et al, 2010. The participants in this study seemed to have a lower mean global fatigue index/GFI (22.99), ranging from 10 -44 on the MAF than several studies in USA (29.8 to 35.08) (Jeon and Redeker, 2016, Redeker et al, 2010b, Redeker et al, 2012, Fritschi and Redeker, 2015. Findings from another study by Nasiri et al (2016) revealed a lower score of GFI among patients with HF in Iran (5.92).…”
Section: Discussioncontrasting
confidence: 44%
“…Although the reviewed studies provide evidence of a relationship between decreased sleepiness symptoms and the combination of HF (Jeon & Redeker 2016; and low energy (Skotzko, 2009), and do not adequately control for potential confounders. Studies also do not consistently explore beta blockers, which are commonly used in heart failure and contribute to fatigue (Fotino, Thompson-Paul, & Bazzano, 2013;Kishi, Watanabe, & Folkers, 1977) (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the reviewed studies provide evidence of a relationship between decreased sleepiness symptoms and the combination of HF and OSA, further investigation is needed to understand the mechanism. The current epidemiologic studies have methodologic flaws and inconsistencies: they have small samples, do not consistently control for fatigue, use various measures of sleepiness and heart failure definitions, do not compare sleepy (ESS >10) versus non‐sleepy groups in the main analyses , do not consider insomnia, which may worsen symptoms of heart failure such as fatigue (Jeon & Redeker ; Redeker et al, ) and low energy (Skotzko, ), and do not adequately control for potential confounders. Studies also do not consistently explore beta blockers, which are commonly used in heart failure and contribute to fatigue (Fotino, Thompson‐Paul, & Bazzano, ; Kishi, Watanabe, & Folkers, ) (see Table ).…”
Section: Conclusion and Future Implicationsmentioning
confidence: 99%
“…In this sample, approximately half of the total sample ( N = 173) had significant SDB (Redeker, Muench, et al, ), and half had insomnia symptoms that were not explained by SDB (Redeker, Jeon, et al, ). We previously reported the associations between SDB, insomnia, daytime symptoms and function (Jeon & Redeker, ; Redeker, Jeon, et al, ; Redeker, Muench, et al, ), and the associations between nocturia and sleep (Redeker et al, ). This study was approved by the IRB, and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 96%